2014
DOI: 10.1007/s00586-014-3274-2
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic spinal cord compression as a result of the unknown primary tumour

Abstract: In our series, the incidence of MSCC due to an unknown primary was 6 %. They had similar overall outcome (neurology post-operatively, complications and survival) to those patients with MSCC from a known primary. Our experience would suggest that we need to treat these patients expeditiously with thorough evaluation and urgent treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Radiotherapy and chemotherapy using as adjuvant treatment for spinal MPG were usually advocated [2,12,29,30]. Radiotherapy with a total of 30-50 Gy had been reported to be helpful for the treatment of spinal MPG [2,6,12,15,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy and chemotherapy using as adjuvant treatment for spinal MPG were usually advocated [2,12,29,30]. Radiotherapy with a total of 30-50 Gy had been reported to be helpful for the treatment of spinal MPG [2,6,12,15,30].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy with a total of 30-50 Gy had been reported to be helpful for the treatment of spinal MPG [2,6,12,15,30]. Mertens et al [28] had reported initial chemotherapy including cyclophosphamide, vincristine and dacarbazine could alleviate symptoms at metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…2012, Quraishi et al. 2014) that have suggested that the prognosis differs between patients whose primary tumor is located and patients whose primary tumor remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…2012, Quraishi et al. 2014). The difference may be explained to some extent by the different patient material with a high percentage of patients with prostate cancer, myeloma, and lymphoma—and consequently by a higher detection rate of primary tumors in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation